NEO-SIYASAH: RECONSTRUCTING CONSTITUTIONAL SOVEREIGNTY IN THE AGE OF ARTIFICIAL INTELLIGENCE - Nawawi, Badruzzaman; Nurdin, Roswati (Jurnal Al-Dustur, 2025)
Artificial intelligence and global digital platforms increasingly erode traditional notions of territorial sovereignty, exposing constitutional deficiencies in regulating algorithmic decision‑making and the exercise of public power. This study proposes the Neo‑Siyasah paradigm, a digital constitutional framework that integrates modern constitutional theory with the ethical principles of Islamic governance. The framework is built through a conceptual‑normative methodology that combines comparative constitutional analysis—drawing on instruments such as the GDPR, the EU AI Act, jurisprudence of the Court of Justice of the European Union, and UNESCO’s ethics guidelines—with normative synthesis rooted in fiqh siyāsah and maqāṣid al‑sharīʿah. From this dual approach, five transformative shifts are identified: digital sovereignty replacing territorial control, digital rights evolving into constitutional entitlements, artificial intelligence functioning as a quasi‑political entity, sovereignty‑by‑design becoming a constitutional necessity, and global AI ethics converging with Islamic legal principles. These shifts culminate in the triadic Neo‑Siyasah model, which consists of an augmented Digital Bill of Rights, sovereignty‑by‑design mechanisms, and constitutional limits on AI authority. Together, these elements establish a coherent framework for legitimacy, fairness, and accountability in algorithmic governance. The model is particularly relevant for Muslim‑majority constitutional regimes, offering a pathway to reconcile global digital transformations with Islamic jurisprudential ethics.